螺旋锥齿轮数字化滚动检验运动模型的推导与实验研究 - 谢建军; 魏冰阳; 杨宏斌 (Jixie chuandong)
Base situation of rolling test of bevel gears are introduced,numeric motion model of rolling inspection are deduced through meshing relation of tooth surface,experiment on mechanical rolling tester are proved effectively.The result is important reference for opening numerical control transformation of machine tool.